A Comprehensive Study of Vehicle Routing Problem With Time Windows Using Ant Colony Optimization Techniques - Guha Neogi, Avirup; Mounika, Singamreddy; Kalyani, Salagrama; A. Yogananda Sai, S (International Journal of Engineering and Technology, 2018)
Ant Colony Optimization (ACO) is a nature-inspired swarm intelligence technique and a metaheuristic approach which is inspired by the foraging behavior of the real ants, where ants release pheromones to find the best and shortest route from their nest to the food source. ACO is being applied to various optimization problems till date and has been giving good quality results in the field. One such popular problem is known as Vehicle Routing Problem(VRP). Among many variants of VRP, this paper presents a comprehensive survey on VRP with Time Window constraints(VRPTW). The survey is presented in a chronological order discussing which of the variants of ACO is used in each paper followed by the advantages and limitations of the same.Â Â